Políticas Culturais e Gestão Cultural: a Secretaria Municipal da Cultura e do Turismo SEMUC (2005-2010) de Limoeiro do Norte-CE - Moura, José Gledson Nogueira (2011)
The study analyzed regarding cultural policies developed in the city of North-EC Limoeiro by the Municipal Culture and Tourism (Semuc) in the period between the years 2005 and 2010. Period that marks the resumption of the figure of the State Ministry of Culture (MinC) as a major factor in formulating and implementing public policies in the area of culture in the country, especially with the creation of the National Culture System (CNS) and the preparation of National Culture Plan (NCP). The work was through research documents (laws) about what had legislated on culture in the city, the reports of consultation activities undertaken by Semuc and interviews with former managers, a former - employee and the Secretary of that folder. Thus, given the contemporary context where the culture is replaced by increasing visibility, the analysis undertaken on policies developed by cultural Semuc revealed the most diverse forms of action: investment in events (capture and promotion), the institution permanent cultural policies, cultural background, the appreciation of local culture, and specific actions